A rhodamine-based 'turn-on' Al3+ ion-selective reporter and the resultant complex as a secondary sensor for F− ion are applicable to living cell staining1. Issue 18 (14th May 2015) - Sen, Buddhadeb; Mukherjee, Manjira; Banerjee, Samya; Pal, Siddhartha; Chattopadhyay, Pabitra
<x xml:space="preserve">Abstract</x> A new cell permeable rhodamine based Schiff base (L) senses nanomolar level of Al3+ ions through CHEF process and its Al(iii) complex (2) behaves as a highly F− ions selective biomarker through fluorescence quenching in HEPES buffer.